The Application of Digital Technologies to Enterprises and Organizations Will Help Reduce Social and Economic Costs - Abdullajonov Davronjon Shokirjon o‘g‘li; Tolipov Umidjon Solijon o‘g‘li (Genius Journals, 2022)
Today, digital knowledge and modern information technologies are one of the important conditions for development. Digital technologies not only improve the governance of the state and society, but also create great conveniences for people in the social sphere. In addition, digital technologies lay the groundwork for positive economic growth: improving the quality of products and services, and reducing unnecessary costs, and another important advantage - putting an end to corruption
Keywords: Digitalization; IT platforms; economic development; electronic services